ASUHAN KEPERAWATAN KOMUNITAS PADA PASIEN HIPERTENSI DENGAN PEMBERIAN TERAPI PMR DI KELURAHAN GEMBOR - Siti Robeatul Adawiyah; Sindri Disti Sagitari; Siti Nurubaidilah; Septa Yundari; Siti Hapsah; Naditya Rahmawati; Waspah Pitriyah; Via Fauzia; Siti Hayatun Najah; Siti Fatimah; Mila; Cut Indah Rahmadani; Laraswati Putri Basuki; Siti Maharani; Ardina Nurfadillah Febianah; Rizma Aulia Putri (Yayasan Nusantara Hasana Berdikari, 2023)
Community is a group of people who have equal values, attention (interest) which is a special group with clear geographical boundaries, with norms and values that have been institutionalized (Sumijatun et al, 2019). Hypertension or high blood pressure is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg on two measurements measurement with an interval of five minutes in a state of adequate rest or calm (Ministry of Health RI, 2020). PMR is done through two processes, namely tense and relax the body's muscles. The advantages of the Progressive muscle relaxation technique are reducing stress, muscle tension, back pain, anxiety, neck pain, headaches, lowering blood pressure. Research Design: Using the implementation of PMR Progressive Muscle Relaxation gymnastics). Research Results: Pretest results of knowledge about PMR relaxation techniques as many as 10 people (55.6%), and post test as many as 13 people (72.2%).